2016
DOI: 10.1371/journal.pone.0165588
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Antioxidant, Antimicrobial, and Anti-Inflammatory Activities of South Brazilian Organic Propolis

Abstract: South Brazilian organic propolis (OP), which has never been studied before, was assessed and its chemical composition, scavenging potential of reactive oxygen species, antimicrobial and anti-inflammatory activities are herein presented. Based on the chemical profile obtained using HPLC, OP was grouped into seven variants (OP1–OP7) and all of them exhibited high scavenging activity, mainly against superoxide and hypochlorous acid species. OP1, OP2, and OP3 had the smallest minimal inhibitory concentration (MIC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 47 publications
(55 reference statements)
9
70
0
13
Order By: Relevance
“…These results agree with Kareem et al (2015) who also observed this activity in Iranian propolis against Staphylococcus spp. MBC for EPA (34.3-68.6µg/mL) was similar to Cabral et al (2009) and Rhajaoui et al (2001); lower than Hayacibara et al (2005), Alencar et al (2007) and Tiveron et al (2016) and higher than Santos et al (2002) and Zeighampour et al (2014). According to Cos et al (2006), the ideal anti-infective concentration would be generally below 100µg/ml for extracts, confirming the excellent efficiency of the EPA in relation to EPB and to others studies.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…These results agree with Kareem et al (2015) who also observed this activity in Iranian propolis against Staphylococcus spp. MBC for EPA (34.3-68.6µg/mL) was similar to Cabral et al (2009) and Rhajaoui et al (2001); lower than Hayacibara et al (2005), Alencar et al (2007) and Tiveron et al (2016) and higher than Santos et al (2002) and Zeighampour et al (2014). According to Cos et al (2006), the ideal anti-infective concentration would be generally below 100µg/ml for extracts, confirming the excellent efficiency of the EPA in relation to EPB and to others studies.…”
Section: Discussionsupporting
confidence: 62%
“…In both extracts the total phenol content was higher than the total flavonoids content, a common finding for propolis from Brazil (Alencar et al 2007, Kalogeropoulos et al 2009, Nunes et al 2012, Coelho 2013, Greece, Cyprus (Kalogeropoulos et al 2009), Czech Republic, Ireland and Germany (Al-Ani et al 2018). The total phenol and flavonoids contents observed for EPA were similar to those of Kumazawa et al (2004), El Sohaimy & Masry (2014) and Silva et al (2015), lower than Alencar et al (2007), Cabral et al (2012), Peixoto et al (2012) and El Sohaimy & Masry (2014), and higher than Tiveron et al (2016). Cunha et al (2004) observed a variation of 6.41 to 15.24% in the total phenol content, while Gonsales et al (2006) verified variations between 0.05 and 0.63% in the contents of flavonoids and Sousa et al (2007) verified a total flavonoid content of 0.06 to 0.38% for samples from São Paulo (Franca region) and from 0.12 to 2.11% for those from Minas Gerais (Passo region).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Trusheva et al (2006) reported that the caffeic extract isolated from red propolis from Alagoas presented antioxidant activity up to 85% compared to positive control phenylhydrazine. In a study involving organic propolis from southern Brazil, Tiveron et al (2016) reported high antioxidant activity of their alcoholic extracts. Other authors evaluated the antioxidant effect of the alcoholic extract of red propolis.…”
Section: Pharmacological Actionmentioning
confidence: 99%
“…Among apiculture products, propolis stands out because it has been traditionally used for centuries (Tiveron et al, 2016). It is a resinous substance with characteristic aroma, whose color varies from yellowish, light greenish red to dark brown, depending on its botanical origin.…”
Section: Introductionmentioning
confidence: 99%